Effect of bonding parameters on microstructural characteristics during TLP bonding of directionally solidified Ni-based superalloy. (December 2017) - Kim, Jeong Kil; Park, Hae Ji; Shim, Deog Nam; Kim, Dong Jin
Abstract: Transient liquid phase bonding (TLP) is well-known to be essential technology to repair damaged components for gas turbines. In this article, directionally solidified γ′-precipitation strengthened GTD-111 superalloy was TLP bonded using Ni-Cr-Si-B filler metal and the effect of bonding parameters on microstructure of the joints was investigated. Isothermal solidification was not completed for the joint bonded at 1150 °C for 60 min, and this joint consisted of three distinct zones: the athermal solidication zone, the isothermal solidification zone and the diffusion affected zone. A phase-free TLP joint, solidified isothermally, was attained at 1150 °C for 90 min and the crystallographic orientation of the ISZ coincided exactly with that of the base metal. Various phases of Ti were observed in the joints formed at 1170 °C and 1190 °C, indicating that temperatures higher than 1170 °C induce a reduction of the isothermal solidication rate. It was found that increase in Ti concentration and decrease in B diffusivity in the joints bonded at temperatures above 1170 °C was the main reason for this reduction.